The Influence of Racket Sports on Longevity and Comprehensive Health Benefits - Dylik, Adrianna; Krawczak, Łukasz; Gulaczyk, Hanna; Spychalska, Maria; Spychalski, Jan; Musiał, Mikołaj; Kaczmarek, Mikołaj; Grochowska, Wiktoria; Gryczyńska, Weronika (Quality in Sport, 2025)
​​Introduction and aim: Physical activity is one of the key components of human life, essential for maintaining health. Racket sports, which emphasize endurance and coordination while engaging a larger number of participants, are increasing in popularity. The aim of this work is to analyze the impact of racket sports on human health in comparison to individual sports. Materials and methods: The analysis is based on a thorough review of peer-reviewed literature published between 2006 and 2025, ensuring the inclusion of the most up-to-date insights. Knowledge was sourced from PubMed, Google Scholar and Scopus using the advanced search with terms „racket sports” with „and” and „health”, ultimately returning 2769 results. Results and conclusion: Racket sports offer significant health benefits, including improved cardiovascular function and musculoskeletal health, while also promoting mental well-being and social engagement. The interactive nature empowers social connections which are crucial for mental health, particularly preventing loneliness and depression. While the risk of injury exists, preventive measures may ensure continued benefits of these sports, making them an excellent choice for promoting health and longevity.